The Implementation Of Problem Based Learning and Jigsaw Model Learning to Improve Basic Programming Learning Outcomes - Erma Widayanti (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
Basic Programming Learning in class X RPL1 in semester 1 has implemented the Problem Based Learning model and runs effectively until it reaches 90% results reaching KKM. Problems occur when there are changes in students in semester 2 because of the industrial class. School regulations state that industrial classes are students who are selected based on psychology and grades in semester 1. In semester 2 industrial classes are placed in class X RPL2 and students who do not enter the industrial class are made one in class X RPL1. The application of the Problem Based Learning model that was implemented previously became less effective, the data at the beginning of semester 2 there were no students from X RPL1 who reached KKM (Minimal Completeness Criteria). This type of research is a classroom action research (CAR). This study aims to measure the feasibility of the learning model and improve the learning outcomes of Class X RPL1 students on Basic Programming subjects by providing innovative learning models that combine the Problem Based Learning and JIGSAW models. The study was conducted in class X RPL 1 of SMK Turen, amounting to 34 students and carried out for 3 cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The results obtained, the feasibility of learning models in the first cycle reached 64%, in the second cycle amounted to 76%, and in the third cycle reached 92%. Learning outcomes in the first cycle of knowledge are the average value of students is 62.94 with a percentage of completeness of 44.12%. In cycle II has increased, the average value of students is 73.52 with a percentage of mastery learning by 70.59%, while in cycle III the average value of students is 79.71 with a percentage of completeness of 91.18%. Based on the results of the study it can be concluded that the implementation of the Problem Based Learning method and the JIGSAW model are able to improve the learning outcomes of Grade X RPL1 students in the Basic Programming of SMK Turen.